ANALYSIS OF COMMUNITY PERCEPTION OF PUBLIC SERVICE QUALITY IN OFFICE SOCIAL INSURANCE ADMINISTRATION ORGANIZATION OF HEALTH (BPJS HEALTH) SURAKARTA CITY - Mardiyanto, Doni (International Journal of Economics, Business and Accounting Research (IJEBAR), 2018)
Public perceptions of the quality of government services in Indonesia generally assess service performance is not as expected, this can be seen, among others, from the many complaints or complaints from the community such as procedures and service mechanisms that are convoluted, not transparent, uninformed, less accommodative, less consistent, limited facilities, service facilities and infrastructure, so that it does not guarantee certainty (law, time, and costs) and there are still many practices of illegal levies and actions that indicate irregularities and service learning. The public perception of the implementation of public services at the Health Social Security Agency (BPJS) is still unknown, whether it resembles a public complaint, considering that government-owned enterprises are more oriented to public services rather than mere benefits. Therefore there is a need for a study to analyze how the public perception of service delivery. This research was conducted at the Office of the Surakarta City Social Security Agency (BPJS), with the aim of analyzing community perceptions of public service delivery and knowing the factors that influence the quality of public services. This study uses a quantitative approach with quantitative descriptive research methods, with survey techniques, namely the distribution of questionnaires to 48 respondents using the Surakarta City Health BPJS service. From the results of the analysis, it is known that the public perception of the users of public services at the Surakarta City Health Insurance Agency (BPJS) Office stated that the implementation of public services was satisfactory. The factors that influence the quality of public services at the Health Social Security Organizing Agency (BPJS) in Surakarta City are factors of education and income. Keywords : Community Perception, Quality and Factors of Public Service.